The Contribution of Abu Nasr Al-Farabi’S Spiritual Heritage Throughout the Virtuous Personal Development - Baizhuma, Samet; Bishmanov, Kakimzhan; Meirbayev, Bekzhan; Baitenova, Nagima; Mukan, Nurzat; Alikbayeva, Marzhan (Journal of Posthumanism, 2025)
“The concept of perfect person” (Insan al-Kamil) in the spiritual heritage of Al-Farabi is one of the most topical challenges due to the constant ongoing changes in moral standards. Above all, the rapid social evolution of human civilization necessitates the development of a dynamic, imaginative personality. Consequently, a variety of scientific domains take into account the examination of theoretical research and the broad notion of personality. Ethical development throughout socio-historical growth results in the perfectness of an individual. Personal characterization heavily relies on the development of persona; in sense, it offers extremely conscious means for acting and behaving, consolidating all of their relationships with realities. The majority of research fields have been built on this perspective. The authors take note of ideals based on Al-Farabi's heritage that are focused on the perfect person (goals and desires, hopes and their expectations, morality and benevolence). Therefore, according to Al-Farabi's spiritual heritage where a perfect person is primarily an individual who is the focus of societal communication and intentional behaviors. Furthermore, it signifies a continuous aspect of the person which relies on their social relations, and serves as the foundation for spiritual harmony.